Aceleración en la obtención del genotipo a2a2 del gen de la beta caseína de la leche mediante superovulación y transferencia de embriones en la HACIENDA LA ESPERANZA. - Salguero Zamora, Luis Miguel (2023)
In Ecuador, the price paid for a milk liter to the major part of the small and medium producers of cow milk is too low, there is no concordance with the elevated cost of producing a liter of milk. In humans the low ingest of bovine milk has been related to gastric and autoimmune problems associated to the consume of milk in some people. The major part of the supposed β -casein risks come from a sub product of its digestion “beta-casomorphin-7(BCM7)”. Nowadays the ingest of milk with A2A2 β-casein, can be an alternative for those individuals with allergies and milk A1 and lactose intolerance. For the experiment They were selected and genotyped 4 Jersey cows; three of them presented the genotype with the A1A2 beta casein, and one with A1A. It was used genetic material from a male (A Tipper bull from STgenetics with the gen of the A2A2 beta casein homozygous). Through the use of biotechnological tools, the superovulation protocol was applied in the cows which carried the A2A2 genotype, and it was performed the correspondent insemination to the donator. The embryo collect is performed on the day 15 of the superovulation protocol, through the methodology of the close circuit with discontinued flood; the embryos were recovered and morphologically valued, as well as their development stage and their quality. As the result, they were obtained six viable embryo, it was done a biopsy and it was worked with trophoblast cells for the qPCR test from the β -casein, obtaining as a result the 33% (2) embryos are carriers of the A2A2 beta casein gen and the 66% (4) embryos are carriers of the A1A2 gen. Therefore, it is suggested that is possible the accelerated multiplication of the A2A2 Gen. Proving that the time for obtaining milk producers animals with the A2A2 beta casein can be shortened through the application of superovulation of the genotyped cows and A2A2 embryo obtention to be transferred to receptors.